ОПТИМІЗАЦІЯ ЕНЕРГЕТИЧНИХ ХАРАКТЕРИСТИК ТРИФАЗНОЇ ЧОТИРИПРОВІДНОЇ СИСТЕМИ ЖИВЛЕННЯ З ПАРАЛЕЛЬНИМ АКТИВНИМ ФІЛЬТРОМ У НЕСИМЕТРИЧНОМУ СИНУСОЇДНОМУ РЕЖИМІ - Артеменко, М.Ю.; Батрак, Л.М.; Михальський, В.М.; Поліщук, С.Й. (Інститут електродинаміки НАН України, Київ, 2015)
The solution of some extreme problems for parameters that determine the energy performance of the three-phase power supply system in the sinusoidal unbalanced mode has been proposed: determination of total power and its quadratic components taking into account the ratio of resistances of the four-wire power cable, minimizing power losses and consumed rms current, maximizing the power factor. These results can be used to develop optimal control strategies of the parallel active filter to compensate the inactive components of total power under conditions of dynamic change of load parameters. References 7, figure 1.